Predicting visual acuity recovery in orbital decompression surgery for dysthyroid optic neuropathy - Forrest W. Fearington; Lazaro R. Peraza; Gabriel A. Hernandez-Herrera; Andrew S. Awadallah; Janalee K. Stokken; Lilly H. Wagner; Elizabeth A. Bradley; Marius N. Stan; Erick D. Bothun; Andrea A. Tooley (Thyroid Research)
Abstract Background Patients with thyroid eye disease may develop dysthyroid optic neuropathy (DON), which is commonly treated via orbital decompression surgery. This study aims to identify preoperative factors that can predict postoperative best corrected visual acuity (BCVA) in patients with DON and to classify recovery rates based on these prognostic factors. Methods We retrospectively assessed thirty-two patients (51 orbits) diagnosed with DON who underwent orbital decompression. Results Univariate and multivariate mixed effects analysis revealed that preoperative BCVA was the strongest predictor of postoperative BCVA (p < 0.0001). Other significant prognostic factors were extraocular muscle hypertrophy (p = 0.01), visual field mean deviation (p = 0.009), retinal nerve fiber layer thickness (p = 0.01), and afferent pupillary defect (p < 0.0001). We then stratified outcomes by the strongest prognostic factor, preoperative BCVA, which demonstrated that 17 of 19 (89.5%) orbits with preoperative BCVA < logMAR 0.20 (20/32 Snellen) achieved acceptable final vision (defined as better than logMAR 0.40 or 20/50 Snellen), compared to 16 of 20 (80%) orbits with preoperative BCVA logMAR 0.20–0.60 (20/32–20/80 Snellen), and only 3 of 11 (27.3%) orbits with preoperative BCVA > logMAR 0.60 (20/80 Snellen). Patients with preoperative BCVA of logMAR 0.60 (20/80 Snellen) or better had > 80% chance of recovering with acceptable final vision after surgery, compared to a < 30% chance for patients with preoperative BCVA worse than logMAR 0.60 (20/80 Snellen). Conclusions These results highlight preoperative BCVA as the strongest predictor of DON outcome and suggest that earlier intervention prior to substantial BCVA deterioration may yield better results. Level of evidence: 3 Retrospectively Registered.